INTRINSIC ELEMENTS OF EKA KURNIAWAN BEAUTY IS A WOUND - Tanwijaya, Donny; Winardi, Yohanes Kurniawan; Fadilah, Eka (Universitas Widya Kartika Surabaya, 2024)
This research aims to analyze the intrinsic elements of Eka Kurniawan's novel Cantik Itu Luka, The study focuses on the character Dewi Ayu, examining the emotions she experiences, including anger, love, sadness, and disgust. By utilizing intrinsic element theory, this research delves into the novel's characterization, plot development, and conflict to uncover how these elements shape Dewi Ayu's complex personality and journey throughout the narrative. This study aims to explore how theauthor portrays Dewi Ayu's struggles and the various emotions that define her character. The findings reveal that Dewi Ayu encounters numerous challenges, each contributing to the richness of her character and the overall narrative. Through a detailed analysis of the intrinsic elements, this research demonstrates how Eka Kurniawan uses these literary techniques to create a powerful and emotionally resonant story. The results offer valuable insights into the deeper layers of meaningwithin the novel, emphasizing the importance of intrinsic elements in shaping the story and its characters.